Exploring urinary microbiome: insights into neurogenic bladder and improving management of urinary tract infections - Zhang, Jinming; Lei, Yingyun; Du, Huayong; Li, Zehui; Wang, Xiaoxin; Yang, Degang; Gao, Feng; Li, Jianjun (Frontiers in Cellular and Infection Microbiology, 2025)
The traditional view of sterile urine has been challenged by advancements in next-generation sequencing, revealing that the urinary microbiome significantly influences individual health and various urinary system diseases. Urinary tract infections in patients with neurogenic bladder are highly prevalent, recurrent, and lifelong. If frequent urinary tract infections are not adequately managed, they may ultimately lead to chronic renal failure. The excessive use of antibiotics to prevent and treat urinary tract infections may lead to increased bacterial resistance, limiting future therapeutic options. This review summarizes commonly used microbiome research techniques and urine collection methods, compiles current studies on the urinary microbiome in neurogenic bladder patients, and discusses the potential implications of urinary microbiome composition for preventing, diagnosing, and treating urinary tract infections. By summarizing current research findings, we aim to enhance understanding of the urinary microbiome in neurogenic bladder patients and promote the standardization and clinical translation of microbiome research.